2009
DOI: 10.2193/2008-225
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation in Lesser Prairie‐Chicken Demography: A Sensitivity Analysis of Population Dynamics and Management Alternatives

Abstract: The lesser prairie‐chicken (Tympanuchus pallidicinctus) is currently considered a candidate for protection under the Endangered Species Act. To identify potential limiting factors for lesser prairie‐chicken populations, we developed an age‐based matrix model of lesser prairie‐chicken population dynamics to compare the relative importance of components of reproduction and survival, and determine if various management alternatives stabilize or increase rates of population change. We based our analyses on an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(99 citation statements)
references
References 33 publications
3
92
4
Order By: Relevance
“…postfledging (i.e., juvenile, SY, and ASY) females had greater prospective ability to affect λ, and made greater retrospective contributions to λ relative to equivalent changes in prefledging vital rates associated with reproductive output. Our results differ from past studies of population dynamics for other tetraonid species, which have generally concluded that reproductive success, especially nest survival, has greater prospective potential to influence λ compared to female survival (Sandercock et al 2005, Tirpak et al 2006, Hagen et al 2009). This can be explained by the fact that sage-grouse are characterized by greater longevity, lower reproductive investment, and a slower overall life history than other tetraonids and most galliformes (Schroeder et al 1999, Saether and Bakke 2000, Taylor et al 2012).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…postfledging (i.e., juvenile, SY, and ASY) females had greater prospective ability to affect λ, and made greater retrospective contributions to λ relative to equivalent changes in prefledging vital rates associated with reproductive output. Our results differ from past studies of population dynamics for other tetraonid species, which have generally concluded that reproductive success, especially nest survival, has greater prospective potential to influence λ compared to female survival (Sandercock et al 2005, Tirpak et al 2006, Hagen et al 2009). This can be explained by the fact that sage-grouse are characterized by greater longevity, lower reproductive investment, and a slower overall life history than other tetraonids and most galliformes (Schroeder et al 1999, Saether and Bakke 2000, Taylor et al 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…However, it is thought that like other ground-nesting birds (Johnson et al 1992, Hoekman et al 2002, Hagen et al 2009), nest survival plays an influential role in population dynamics (Taylor et al 2012). As such, conservation recommendations have often been focused on improving nesting habitat conditions (Johnson and Braun 1999, Connelly et al 2000, Taylor et al 2012, Kirol et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Nest survival is critical to population persistence in Lesser Prairie-Chickens because survival of juveniles from hatch to the following breeding season has been identified as the key demographic parameter associated with population declines (Hagen et al 2009). Despite the wavering status of the species on the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…Campbell (1972) studied the sex ratio of first year LEPC observed in fall harvests from 1958 to 1968, reporting a sex ratio of 50.3% male to 49.7% female, which corresponds closely to the standard practice in LEPC models of using a 1:1 sex ratio (Hagen, 2009;Godar, 2016;Griffin, 2016;Sullins, 2017). We follow this standard practice, using a fixed 1:1 sex ratio in our predictive modeling.…”
Section: Appendix B Demographic Rates From Literaturementioning
confidence: 71%